Design analysis of mold cavity and core on compression molding of composite material - Muslimin Al Masta; Hasvienda M. Ridlwan; Dhiya Luqyana; Bayu Pambudi; Azam Milah Muhamad (Politeknik Negeri Lhokseumawe, 2023)
This study discusses the design analysis of compression molding cavity and core under 12 tons of pressure and 100oC heat using experimental analysis and Ansys R19.2 simulation. This compression mold is used to process composite materials, mainly thermoset matrix composites. The compression product is a tensile test specimen according to the ASTM D638-4 standard. The main concern of this study aimed to analyze the stress distribution and deflection due to the compression load and heat on the cavity and core of compression molding. Hence, the die construction is safe during the operation under these loads. The analysis was carried out using Von Mises's stress of static loading criteria. The research parameter examined are stress distribution, deflection, and some critical dimensions in the cavity and core. These parameters significantly affect mold performance, product quality, and service life. Experimental analysis shows that the maximum deflection of the cavity and the core is 4.40 x10-4 mm and 1.53 x 10−4 mm, respectively. On the other hand, Simulation analysis shows the maximum deflection of the cavity and core is 4.56 x 10−4 mm and 7.41 x 10-5 mm, respectively. The error between experimental analysis and simulation is 6.87 x 10-5 mm and 3.32 x 10-5 mm for the cavity and the core, respectively. For stress analysis, the maximum value is 37.94 MPa for both cavity and core. On the other hand, simulation analysis shows 262 MPa and 256 MPa for the cavity and core, respectively. Both experimental analysis and simulation show that the result complies with the standard, less than 0,025 mm for deflection, and stress is less than 1034 MPa for maximum stress. Therefore, compression mold structure is safely used.